(untitled) («Наука и здравоохранение», 2026)
In this work shows the case of detection of Kartagener syndrome of the newborn child. This is a rare hereditary disease, route of transmission is autosomal recessive and is characterized by a triad of symptoms: the reverse arrangement of internal organs, chronic bronchopulmonary process and sinusorinopatiya.